Research on temperature field and heat dissipation development regularity of surrounding rock in adjacent parallel roadway: Simulation and similar experiment - Fei Tang; Yueping Qin; Mingyan Guo; Shibin Wang; Peng Wang; Yanjie Yang (Case Studies in Thermal Engineering)
As mining activities deepen, thermal hazards in mines are increasingly severe, with heat dissipation from surrounding rock (SR) being a critical factor. This study examines the temperature distribution and heat release evolution of SR in adjacent parallel roadway (APR). A mathematical model was developed for the surrounding rock temperature field (SRTF) in APR, and the finite volume method (FVM) was employed for discretization. An independently developed numerical solver was validated against simulation experiments, showing high accuracy with a maximum relative error of 1.92 %. The findings reveal that: (i) The heat-regulating circle (HRC) of APR forms an elliptical distribution, with SR temperature symmetrically distributed on both sides of the origin. (ii) Closer to roadway walls, a sharper temperature decline occurs. An adiabatic boundary along APR's symmetry axis restricts heat dissipation. After a one-year ventilation period, the heat flux difference between a single roadway and APR is 0.848 W/m2. (iii) Heat dissipation can be reduced by decreasing roadway distance, lowering initial rock temperature, and reducing thermal conductivity, thereby mitigating mine heat damage. This research provides a theoretical basis for the prevention and management of heat hazards in APR within underground mining spaces.